Gender Role Models and Early Career Decisions - Monique Löwe; Ulf Rinne; Hendrik Sonnabend (Institute of Labor Economics (IZA), 2021)
This paper analyzes the link between the subject choices of German students in upper secondary school and teacher gender when these choices are taken. Our results corroborate the hypothesis that teacher gender matters in this regard, and they indicate that girls respond more strongly than boys to same-sex role models. While the probability to choose German as an advanced course in upper secondary school increases to a rather similar (i.e., symmetric) extent for both girls and boys when having a same-sex teacher in this subject in grade 10, teacher gender matters only for girls with respect to choosing math on the advanced level.
Keywords: I21; J16; J24; 330; gender; education; STEM; subject choices